Vitamin-D status and metabolic syndrome in patients with type 2 diabetes mellitus - Shrestha, Pradeep; Rauniyar, Nabin Kumar; Sharma, Lucky; Adhikari, Krishna (Journal of General Practice and Emergency Medicine of Nepal, 2024)
Introduction: Vitamin-D, besides its role in calcium and phosphorus homeosta-sis, has been increasingly recognized to affect various other metabolic process-es including insulin secretion and sensitivity. Thus, Vitamin-D has a potential role in development of type 2 diabetes mellitus and metabolic syndrome. This study aims to evaluate the status of Vitamin-D and metabolic syndrome among patients with type 2 DM. Method: This is a hospital based cross-sectional observational study conducted at Bir Hospital, Kathmandu, Nepal from October 2017 to March 2018. Adult patients above 18 years with newly diagnosed type 2 diabetes or those already diagnosed and under medication were included in this study. Baseline charac-ters, Vitamin-D status, metabolic syndrome were evaluated. Statistical package for social sciences (SPSS) version 20 was used for data analysis. Result: Fifty-eight participants; 38 (65.52%) males and 20 (34.48%) females were enrolled. Fifty-two (89.67%) participants had low Vitamin-D levels (either deficiency or insufficiency). The mean vitamin D level was 18.78 ng/ml. Metabolic syndrome was seen among 37 (63.8%) participants. Low Vitamin-D (deficient or insufficient) was more common among those with metabolic syndrome (97.3%) compared to those without metabolic syndrome (76.19%). Conclusion: Type 2 diabetes patients have high prevalence of hypovitaminosis D and metabolic syndrome. Vitamin-D deficiency is more common in those with metabolic syndrome.